2019
DOI: 10.3201/eid2503.181597
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nontuberculous Mycobacterial Infection, South Korea, 2007–2016

Abstract: The prevalence and incidence of nontuberculous mycobacterial (NTM) infections increased in South Korea from 2007 to 2016. Annual prevalence of NTM infection increased to 39.6 cases/100,000 population in 2016 and annual incidence to 19.0 cases/100,000 population. Overall prevalence for the study period was higher in the elderly, in females, and in cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 15 publications
8
84
0
4
Order By: Relevance
“…In this retrospective study, M. intracellulare (65/193, 33.7%) was the most commonly detected species in respiratory tract samples, followed by M. chelonae / M. abscessus (37/193, 19.2%), M. avium (27/193, 14.0%), M. gordonae (24/193, 12.4%). So in this study, MAC (92/193, 47.7%) was still the most common NTM pathogen in respiratory tract, which is consistent with previous findings in Europe, US, Canada, Australia, Japan, Korea, Southern China and so on (18)(19)(20)(21)(22)(23). Although MAC is the most common pathogen in NTM pulmonary disease, its relative frequency varies widely among different geographical regions.…”
Section: Ntm Species Distribution From Different Specimen Typessupporting
confidence: 91%
“…In this retrospective study, M. intracellulare (65/193, 33.7%) was the most commonly detected species in respiratory tract samples, followed by M. chelonae / M. abscessus (37/193, 19.2%), M. avium (27/193, 14.0%), M. gordonae (24/193, 12.4%). So in this study, MAC (92/193, 47.7%) was still the most common NTM pathogen in respiratory tract, which is consistent with previous findings in Europe, US, Canada, Australia, Japan, Korea, Southern China and so on (18)(19)(20)(21)(22)(23). Although MAC is the most common pathogen in NTM pulmonary disease, its relative frequency varies widely among different geographical regions.…”
Section: Ntm Species Distribution From Different Specimen Typessupporting
confidence: 91%
“…However, in other studies including our study, no significant difference of distribution was found between genders 2,10 , and the prevalence of NTM in younger individuals should also be given attention 6 . The difference of prevalence between genders may be due to the heterogenicity of the infection-causing microorganism among different regions 2 or the distribution of ages between genders 19 . In our study, female patients with NTM showed a significantly higher percentage of bronchiectasis than male patients, similar to the results reported by Zhang et al in Singapore 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by nontuberculous mycobacteria (NTM) have increased dramatically worldwide in recent years. [1][2][3][4] Mycobacterium abscessus is one of the most common NTM detected. M. abscessus infections are difficult to manage because M. abscessus is intrinsically resistant to a variety of antimicrobials currently available in clinical practice; infections that are refractory to antibiotic therapy frequently result in morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%